Assessment of School-Based Quasi-Experimental Nutrition and Food Safety Health Education for Primary School Students in Two Poverty-Stricken Counties of West China. - Minxue Shen; Ming Hu; Zhenqiu Sun (PLoS ONE)
Background Few studies on nutrition and food safety education intervention for students in remote areas of China were reported. The study aimed to assess the questionnaire used to measure the knowledge, attitude and behavior with respect to nutrition and food safety, and to evaluate the effectiveness of a quasi-experimental nutrition and food safety education intervention among primary school students in poverty-stricken counties of west China. Methods Twelve primary schools in west China were randomly selected from Zhen'an of Shaanxi province and Huize of Yunnan province. Six geographically dispersed schools were assigned to the intervention group in a nonrandom way. Knowledge, attitude and behavior questionnaire was developed, assessed, and used for outcome measurement. Students were investigated at baseline and the end of the study respectively without follow-up. Students in intervention group received targeted nutrition and food safety lectures 0.5 hour per week for two semesters. Item response theory was applied for assessment of questionnaire, and a two-level difference-in-differences model was applied to assess the effectiveness of the intervention. Results The Cronbach's alpha of the original questionnaire was 0.84. According to item response model, 22 knowledge items, 6 attitude items and 8 behavior items showed adequate discrimination parameter and were retained. 378 and 478 valid questionnaires were collected at baseline and the end point. Differences of demographic characteristics were statistically insignificant between the two groups. Two-level difference-in-differences models showed that health education improved 2.92 (95% CI: 2.06-3.78) and 2.92 (95% CI: 1.37-4.47) in knowledge and behavior scores respectively, but had no effect on attitude. Conclusion The questionnaire met the psychometric standards and showed good internal consistence and discrimination power. The nutrition and food safety education was effective in improving the knowledge and behavior of primary school students in the two poverty-stricken counties of China.